Role of the Carotid Bodies in the Hypertensive and Natriuretic Responses to NaCl Load in Conscious Rats - da Silva, Elaine Fernanda; de Melo, Aryanne Batista Soares; Lobo Júnior, Eulício de Oliveira; Rodrigues, Karla Lima; Naves, Lara Marques; Coltro, Wendell Karlos Tomazelli; Rebelo, Ana Cristina Silva; Freiria-Oliveira, André Henrique; Menani, José Vanderlei; Pedrino, Gustavo Rodrigues; Colombari, Eduardo (Frontiers in Physiology, 2018)
Hyperosmotic challenges trigger a hypertensive response and natriuresis mediated by central and peripheral sensors. Here, we evaluated the importance of the carotid bodies for the hypertensive and natriuretic responses to acute and sub-chronic NaCl load in conscious rats. Male Wistar rats (250-330 g) submitted to bilateral carotid body removal (CBX) or sham surgery were used. One day after the surgery, the changes in arterial blood pressure (n=6-7/group) and renal sodium excretion (n=10/group) to intravenous infusion of 3 M NaCl (1.8 mL/kg b.w. during 1 min) were evaluated in non-anesthetized rats. Another cohort of sham (n=8) and CBX rats (n=6) had access to 0.3 M NaCl as the only source of fluid to drink for 7 days while ingestion and renal excretion were monitored daily. The sodium balance was calculated as the difference between sodium infused/ingested and excreted. CBX reduced the hypertensive (8 ± 2 mmHg, vs. sham rats: 19 ± 2 mmHg; p<0.05) and natriuretic responses (1.33 ± 0.13 mmol/90 min, vs. sham: 1.81 ± 0.11 mmol/90 min; p<0.05) to acute intravenous infusion of 3 M NaCl, leading to an increase of sodium balance (0.38 ± 0.11 mmol/90 min, vs. sham: -0.06 ± 0.10 mmol/90 min; p<0.05). In CBX rats, sub-chronic NaCl load with 0.3 M NaCl to drink for 7 days increased sodium balance (18.13 ± 4.45 mmol, vs. sham: 5.58 ± 1.71 mmol; p<0.05) and plasma sodium concentration (164 ± 5 mmol/L, vs. sham: 140 ± 7 mmol/L; p<0.05), without changing arterial pressure (121 ± 9 mmHg, vs. sham: 116 ± 2 mmHg). These results suggest that carotid bodies are important for the maintenance of the hypertensive response to acute hypertonic challenges and for sodium excretion to both acute and chronic NaCl load.